Prediction of chemical indicators for quality of Zanthoxylum spices from multi-regions using hyperspectral imaging combined with chemometrics - Wang, Youyou; Yang, Jian; Yu, Shuan; Fu, Haiyan; He, Song; Yang, Bin; Nan, Tiegui; Yuan, Yuwei; Huang, Luqi (Frontiers in Sustainable Food Systems, 2022)
Fruits of Zanthoxylum bungeanum Maxim (Red “Huajiao”, RHJ) and Z. schinifolium Sieb. et Zucc. (Green “Huajiao”, GHJ) are famous spices around the world. Antioxidant capability (AOC), total alkylamides content (TALC) and volatile oil content (VOC) in HJ are three important quality indicators and lack rapid and effective methods for detection. Non-destructive, time-saving, and effective technology of hyperspectral imaging (HSI) combined with chemometrics was adopted to improve the indicators prediction in this study. Results showed that the three chemical indexes exhibited significant differences between different regions and varieties (P < 0.05). Specifically, the mass percentages of TALC were 11-22% in RHJ group and 21-36% in GHJ group. The mass percentages of VOC content were 23-31% and 16-24% in RHJ and GHJ groups, respectively. More importantly, these indicators could be well predicted based on the full or effective HSI wavelengths via model adaptive space shrinkage (MASS) and iteratively variable subset optimization (IVSO) selections combined with wavelet transform (WT) method for noise reduction. The best prediction results of AOC, TALC, and VOC indicators were achieved with the highest residual predictive deviation (RPD) values of 7.43, 7.82, and 3.73 for RHJ, respectively, and 6.82, 2.66, and 4.64 for GHJ, respectively. The above results highlight the great potential of HSI assisted with chemometrics in the rapid and effective prediction of chemical indicators of Zanthoxylum spices.